Multiple Narratives and Postmodern Techniques: A Study of Jorge Luis Borges and Thomas Pynchon - Rafiuddin, Zarin (BRAC University, 2015)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2014.